A collagen‐coated sponge silk scaffold for functional meniscus regeneration. (4th January 2019) - Yan, Ruijian; Chen, Yangwu; Gu, Yanjia; Tang, Chenqi; Huang, Jiayun; Hu, Yejun; Zheng, Zefeng; Ran, Jisheng; Heng, Boonchin; Chen, Xiao; Yin, Zi; Chen, Weishan; et al.
Abstract: Tissue engineering is a promising solution for meniscal regeneration after meniscectomy. However, in situ reconstruction still poses a formidable challenge due to multifunctional roles of the meniscus in the knee. In this study, we fabricate a silk sponge from 9% (w/v) silk fibroin solution through freeze drying and then coat its internal space and external surface with collagen sponge. Subsequently, various characteristics of the silk‐collagen scaffold are evaluated, and cytocompatibility of the construct is assessed in vitro and subcutaneously. The efficacy of this composite scaffold for meniscal regeneration is evaluated through meniscus reconstruction in a rabbit meniscectomy model. It is found that the internally coated collagen sponge enhances the cytocompatibility of the silk sponge, and the external layer of collagen sponge significantly improves the initial frictional property. Additionally, the silk‐collagen composite group shows more tissue ingrowth and less cartilage wear than the pure silk sponge group at 3 months postimplantation in situ. These findings thus demonstrate that the composite scaffold had less damage to the joint surface than the silk alone through promoting functional meniscal regeneration after meniscectomy, which indicates its clinical potential in meniscus reconstruction.